Access to Administrative Justice as an Administrative Law Value: Designing an Inclusive and Accessible Administrative Justice System - Jacobs, Laverne (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
The constantly developing norm of access to justice is moving to occupy a central place in the administrative justice system, prompting a need to rethink the values that should serve to animate the system. This article offers a framework for the administrative justice system in Canada, one that firmly and explicitly entrenches the value of access to administrative justice within it. It reflects on the requirements to achieve access for a significant population of its users – namely, equality-deserving communities. The author looks at the historical reasons why access to justice has been a concern for equality-deserving communities, and introduces the concept of social equity from the discipline of public administration as a tool to assist in addressing some of the structural and systemic access-to-administrative-justice challenges experienced. The author rearticulates the foundational values of administrative law in Canada to incorporate access to administrative justice as a distinct value, one that engages with access-to-justice barriers relating to structural and systemic inequality. In doing so, she details five core principles that underpin the new value of access to administrative justice and cites examples of recent tribunal reform projects in Canada that illustrate promising innovations in that direction. Finally, the author describes briefly the ways in which institutional design and tribunal culture can contribute to enhancing the value of access to administrative justice within the broad, on-the-ground context of different administrative actors. Overall, this article presents an analysis of the dynamic interaction between marginalized populations and the administrative state in order to move forward judicial and other contemporary discussions about access to administrative justice and how it should be defined.